National Security Redesign after the COVID–19: Nepali Army’s Security Priority in Response to the Global Pandemics - Angbo, Padam Kumar (Unity Journal, 2021)
Pandemic disease always poses one of the greatest security threats to national security. It is widely discussed as a non-traditional threat candidate to national security (NDU, CACI, The Asymmetric Threat Symposium, 2008, p. 31). Indeed, the COVID-19 has not only unleashed havoc on developing nation but also provided a vital national security lesson exposing weaknesses in their capabilities to protect citizens. For example, Nepal has lost more than 2000 lives of its people and about 271,000 have severely suffered this viral infection, and the deaths with this pandemic in the US and UK are even higher. And the trend of causalities has increasingly been continuing along with an alarming rate of infection. Meanwhile, a new deadly variant of corona virus is swiftly spreading across the globe including Nepal. This study employs the qualitative research framework and data have been employed from secondary sources. The research philosophy adopted is interpretivism where the researcher has included his viewpoints to available data in presenting ideas. The article explores causes and multi-dimensional effects, critical nexus between COVID-19 and National Security in support to the argument that the nature, scope, novelty and complexity of COVID-19 pandemic demands an Integrated National Security Strategy for an effective application of all the instruments of national power, including Nepali Army, public and private sector to respond successfully. This paper also spotlights the crucial role of Nepali Army in containing pandemics that proffers to reappraisal of such a vital security body’s strategies and doctrines, taking the current corona virus in serious consideration.